2020
DOI: 10.30557/qw000030
|View full text |Cite
|
Sign up to set email alerts
|

Perusall: University learning-teaching innovation employing social annotation and machine learning

Abstract: all algorithm provided scores quite similar to those of the teacher, and that students positively perceived the automated scoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
2
9
0
2
Order By: Relevance
“…This produced growth of critical reading skills among students of the experimental group. The results of the recent study are consistent with those of the studies by Lee & Yeong (2018), Adams & Wilson (2020), Cecchinato & Foschi (2020), McFarlin (2020.…”
Section: Skillssupporting
confidence: 90%
See 1 more Smart Citation
“…This produced growth of critical reading skills among students of the experimental group. The results of the recent study are consistent with those of the studies by Lee & Yeong (2018), Adams & Wilson (2020), Cecchinato & Foschi (2020), McFarlin (2020.…”
Section: Skillssupporting
confidence: 90%
“…Moreover, the more students are engaged in commenting assignments on the Perusall platform, the better is their score on exams. Cecchinato & Foschi (2020) state that students studying habits have changed from a very isolated experience to be a social one due to the use of the Perusall platform in teaching. Students can share their questions and answers on the topics with each other and with the teacher they are studying easily.…”
Section: Study Questionsmentioning
confidence: 99%
“…The Honors general chemistry course described in this investigation is a natural fit for including exam questions in which students critique output from ChatGPT, and this will be implemented next year. To practice this skill, chatbot responses will be placed in the platform Perusall 56 where students work together to identify strengths, weaknesses, and suggest improvements. The use of chatbot generated responses in a class like general chemistry where closed-response exams are used may be less obvious.…”
Section: ■ Instructional Implicationsmentioning
confidence: 99%
“…The SA program used in the present study (Perusall) uses an automated grading system. Cecchinato and Foschi (2020) found that students accepted being graded by an automated process as long as a human instructor supervised it. The researchers also empirically tested the validity of the automated scoring system and found that it was consistent with the instructors' scores.…”
Section: Why Use Social Annotation?mentioning
confidence: 99%